2007
DOI: 10.1111/j.1574-0862.2007.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The economics of natural disasters: implications and challenges for food security

Abstract: A large and growing share of the world's poor lives under conditions in which high hazard risk coincides with high vulnerability. In the last decade, natural disasters claimed 79,000 lives each year and affected more than 200 million people, with damages amounting to almost US $ 70 billion annually. Experts predict that disasters will become even more frequent and their impact more severe, expecting a five-fold global cost increase over the next fifty years, mainly due to climate change and a further concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 3 publications
0
50
1
2
Order By: Relevance
“…Surprisingly, the rank correlation between this impact indicator and all responsibility and capability indicators is insignificant. This result seems to contradict the findings of many other studies, which conclude that poor countries, and poor people in all countries, are most strongly affected by weather-related disasters (Blaikie et al, 2004;de Haen and Hemrich, 2007;Roberts and Parks, 2007), including similar analyses based on mortality data for the 1980-2002 period from the same dataset (Kahn, 2005;Roberts and Parks, 2007). Further analysis reveals that the qualitatively different results between the 1970-2008 period and the 1980-2002 period are caused by the effects of the 2003 European summer heat wave, which caused substantial premature mortality in many high-income countries.…”
Section: Social Impactscontrasting
confidence: 80%
“…Surprisingly, the rank correlation between this impact indicator and all responsibility and capability indicators is insignificant. This result seems to contradict the findings of many other studies, which conclude that poor countries, and poor people in all countries, are most strongly affected by weather-related disasters (Blaikie et al, 2004;de Haen and Hemrich, 2007;Roberts and Parks, 2007), including similar analyses based on mortality data for the 1980-2002 period from the same dataset (Kahn, 2005;Roberts and Parks, 2007). Further analysis reveals that the qualitatively different results between the 1970-2008 period and the 1980-2002 period are caused by the effects of the 2003 European summer heat wave, which caused substantial premature mortality in many high-income countries.…”
Section: Social Impactscontrasting
confidence: 80%
“…The variable HDI represents the Human Development Index, a United Nations (UN) indicator comprised of per capita income, average education and literacy rates, and average life expectancy at birth. Recent studies of disaster losses -not limited to climate-related events-have shown that countries with medium HDI values experience the highest average losses, whereas countries with high HDI values experience the lowest (14,15). We therefore included the logged HDI values in quadratic form.…”
Section: Resultsmentioning
confidence: 99%
“…This worry is especially strong where there is not a well-accepted causal explanation for cross-sectional patterns that would also explain time series effects. The nonmonotonic relationship between HDI and disaster losses-which appears to be a key driver of our results-is one for which a wellaccepted causal explanation is indeed lacking (14,15). Second, all of our climate exposure scenarios rely on an assumption of a linear increase in disaster frequencies over the next 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Increased soil erosion and nutrient depletion associated with climatic variability and environmental change present a threat to food security and the sustainability of agricultural production in parts of sub-Saharan African, with government and development agencies already investing resources to promote soil conservation practices as part of an effort to improve environmental conditions and reduce poverty (Kassie et al 2008). While, for instance, Mueller and Osgood (2009) suggest a link between large precipitation shocks in rural areas and urban poverty, de Haen and Hemrich (2007) also demonstrate how extreme conditions and natural disasters could have significant implications and challenges for food security.…”
Section: Introductionmentioning
confidence: 97%